Enzymes profiling in original and manipulated fermentation of anchovies based fish sauce - Razalee, Nurul Shahida Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Fish sauce is a fermented fish products resulted from hydrolysis of fish protein at certain salt concentration. The objectives of this study were to investigate the enzymes activity, namely protease and amylase, in original fermented fish sauce and manipulated fermented fish sauce. In addition, moisture content, protein (total nitrogen), and pH changes were also measured. One sample of original fermented fish sauce was prepared according to the procedure provided by one of the local factories, Perusahaan Budu Cap Ketereh using fresh anchovies and fish to salt ratio of 2:1. For the manipulated fermented fish sauce, three samples were prepared using the same procedure as the original with fish to salt ratio of 1:1, 1:2, and 2:1. However, instead of using fresh anchovies, dried anchovies were selected for manipulated fish sauce. The amylase activity for manipulated fish sauce in 1:1, 1:2 and 2:1 were 0.77 ±0.14 U/mL, 1.10 ± 0.18 U/mL and 0.95 ±0.12 U/mL respectively, while in original fish sauce, the amylase activity was 1.11 ±01.4 U/mL. The highest protease activity was in manipulated (1:1) fish sauce which was 0.10 ± 0.07 U/mL, followed by manipulated (1:2) with 0.03 ± 0.03 U/mL, manipulated (2:1) with 0.03 ± 0.02 U/mL, and lastly in original fish sauce with 0.01 ± 0.00 U/mL. For moisture content (%), the result for manipulated fish sauce were 39.77 ± 3.57 (1:1), 38.35 ± 4.98 (1:2), and 45.63 ± 8.91 (2:1), and the result for original fish sauce was 51.38 ± 1.08. The protein (total nitrogen) for manipulated fish sauce in 1:1, 1:2 and 2:1 ratio were 4.23 ± 1.06, 4.12 ± 1.50, and 4.27 ± 1.33 respectively, while in original fish sauce, the total nitrogen was 2.58 ± 0.19. For pH changes, the result for manipulated fish sauce were 6.05 ± 0.04 (1:1), 6.02 ± 0.04 (1:2), and 6.01 ± 0.03 (2:1), and the result for original fish sauce was 5.87 ± 0.02. Proteolytic enzymes activity played an important role during fermentation process and pH changes and salt concentration (ratio) were shown to be related to enzymes activity.